Challenges and agroecological approaches in crop production - Berzsenyi, Zoltán (Acta Agraria Debreceniensis, 2018)
Never has the need been greater for an ecosystem approach to agriculture. As our global population exceeds 9 billion in the next 30 years, with a concomitant demand for agricultural products, ever more pressure will be placed on our agricultural systems. Meanwhile, climate change is altering the ecological settings in which agriculture is practiced, demanding adaptation. Knowledge generated by long-term research will help to address one of the grand challenges of our time: how to meet sustainably the growing world demand for agricultural products – in a way that minimizes environmental harm and enhances the delivery of a diverse array of ecosystem services.